Blockchain empowering genomic data management: a short review - Patturajan, Ramya; Narayanan, Venkatesh Babu Sakthi (Asia-Pacific Journal of Science and Technology, 2024)
Recent advancements in genomic research such as genomic sequencing and editing have given incredible benefits for physicians to deliver accurate and precise treatments. But still, there are a few major challenges such as computational and security issues which could suffocate the performance of a system that deals with genomic data storage, sharing, and analysis. Hence, this paper has been presented with the intention of revealing the potential of emerging technologies to solve the aforementioned bottlenecks with appropriate case studies. To understand the significance of cloud computing in the field of genetic engineering, the exploration has been made to discover the various cloud-based solutions that are developed by various academicians and researchers at various time periods for accomplishing effective genomic data storage, sharing, and analysis. From the detailed study, it has been observed that the cloud computing has a scalable resources and infrastructure to resolve computational complexity of genomic data. But it could be identified that there are no prominent features and methods to prevent security breaches. It necessitates the need for blockchain technology which is being considered an optimal solution for handling genomic data securely. Despite its numerous advantages, blockchain technology still presents some notable technological challenges. These include issues related to scalability, high energy consumption, storage overhead, and potential organizational threats. So, in this article, various blockchain frameworks that have been developed so far for genomic data management are explored and facilitate researchers to understand the potential benefits and implementation challenges of blockchain in genomic data management.